If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 5) + 2 = 60 Reorder the terms: 3(5 + n) + 2 = 60 (5 * 3 + n * 3) + 2 = 60 (15 + 3n) + 2 = 60 Reorder the terms: 15 + 2 + 3n = 60 Combine like terms: 15 + 2 = 17 17 + 3n = 60 Solving 17 + 3n = 60 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 3n = 60 + -17 Combine like terms: 17 + -17 = 0 0 + 3n = 60 + -17 3n = 60 + -17 Combine like terms: 60 + -17 = 43 3n = 43 Divide each side by '3'. n = 14.33333333 Simplifying n = 14.33333333
| 4w-6= | | .20*40= | | n^2=6n+72 | | b/4+5=14 | | x+y=130 | | a/9=6 | | -7=11+x | | 2x-5x=-6 | | 3*76= | | (9x-81)=12 | | 34/6=2x+1/3 | | 3x^2-2x-12x+8= | | 3x+y=130 | | 6y=30y+140 | | 2abc+d=3 | | -5y-2y+3y=9 | | -19-(-4)=x | | -10-(-5)=x | | -18=6x-4x | | 3/4=z/16 | | 2a+-5b+5a+-1b= | | c^2=40-3c | | 8x-9+7x= | | 55=5/9(f-32) | | 7-3x=5x | | 2a-7=1 | | 3(x+3)=4(x-1) | | (-3y+18)=y | | 4a-6(a+1)=2(a+5) | | 4(2n-7)=12 | | 4/7+15= | | 3(2n-8)=4(-1-n) |